2013
DOI: 10.1179/204777213x13777615588180
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in a tertiary health care facility of Central India with special reference to severe vivax: implications for malaria control

Abstract: Plasmodium vivax is now recognized as a cause of severe and fatal infection in many parts of the world. This prospective observational study was undertaken in a tertiary health setting to understand the spectrum of the disease burden and associated complications due to P. vivax malaria in central India. A malaria clinic under Regional Medical Research Centre for Tribals is operational at Netaji Subhash Chandra Bose Medical College and Hospital, Jabalpur in central India, where all fever cases and cases with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…Lactate, hypoglycaemia, and metabolic acidosis, all of which are important indicators of severe malaria, were not routinely measured due to existing hospital practices. Malaria patients admitted to the GMC who required use of a ventilator, presumably due to respiratory distress [29, 47], which also has been commonly reported in severe P. vivax, were not included in the present study. This may impact the disease burden being reported among P. vivax and/or P. falciparum cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactate, hypoglycaemia, and metabolic acidosis, all of which are important indicators of severe malaria, were not routinely measured due to existing hospital practices. Malaria patients admitted to the GMC who required use of a ventilator, presumably due to respiratory distress [29, 47], which also has been commonly reported in severe P. vivax, were not included in the present study. This may impact the disease burden being reported among P. vivax and/or P. falciparum cases.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Africa, malaria transmission in India is more limited, both adolescents and adults are at risk of severe malaria, and a substantial proportion of cases are infected with P. vivax rather than the traditionally more virulent P. falciparum . Although many expansive and comprehensive studies have been carried out in Africa [914] and Southeast Asia [1520] to examine pathogenesis and mortality determinants in malaria-positive patients, a more limited number of such studies, generally smaller in scope, have been conducted within India [21–29]. …”
Section: Introductionmentioning
confidence: 99%
“…Malaria remains a major public health problem worldwide. Plasmodium falciparum is the parasite species causing the lethal form of the disease whilst Plasmodium vivax has long been considered a parasite causing mild disease, thereby diverting attention away from this species regarding research; however, recent studies have reported that this species also causes severe clinical syndromes [ 1 , 2 ]. Even though both species infect humans, they both emerged from different evolutionary lineages; whilst P. vivax shares a common ancestor with Asian non-human primate malaria, P. falciparum has diverged from parasites infecting great apes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…69 Previously, it was thought that falciparum malaria is more dangerous; however, some recent studies have broken the myth and have shown that even vivax malaria is associated with various complications in children. [76][77][78] Rarely, malaria can also present with acute demyelinating encephalomyelitis in young children. 79,80 Microscopic examination of peripheral blood smear remains the gold standard for diagnosis.…”
Section: Malariamentioning
confidence: 99%